The diet of bats in forest ecosystems and their potential as natural enemies of forest pests: A case study in the Khingan Mountains, Northeast China - Lixin Gong; Zhiqiang Wang; Can Ke; Maojun Zhong; Wenhao Zhang; Yaping Lu; Kangkang Zhang; Jiang Feng; Tinglei Jiang (Ecological Indicators)
The health and integrity of the forest ecosystem are critical to maintaining its stability, biodiversity, and ecological services. Bats, as natural predators of pests in agroforestry ecosystems, provide pest control services. However, most studies have focused on agroecosystems, but studies on forest ecosystems are scarce. Here, we determined the dietary composition and diversity of forest bats in the Lesser and Greater Khingan Mountains (LKM and GKM) of Northeast China via DNA metabarcoding. We also identified the species and diversity of forest pests consumed by bats and determined the relationships of bat body size, population size, and dietary diversity with the number and diversity of consumed forest pests. The results showed that the diets of 92 individuals of eight bat species comprised 12 orders of arthropods, dominated by Lepidoptera, Diptera, and Hemiptera. In total, 238 forest pest items belonging to 97 species were detected in bat diets, representing about 31 % of identified prey species. Bats in the LKM preyed mainly on forest pests belonging to the Noctuidae family, whereas those in the GKM belonging to the Tortricidae family. Additionally, a significant positive correlation was found between the richness and Shannon diversity of the bat diet and those associated with the consumption of forest pests. The population size of the captured bat species was significantly positively correlated with the number of forest pests consumed. These findings suggest that forest bats are potential natural enemies of forest pests and that the population size and degree of dietary diversity of bats may play crucial roles in pest control services in forest ecosystems. This study provides novel insights into the role of bats as natural solutions in forest ecosystems and highlights the importance of conserving forest bats and their integration into integrated pest management practices in forestry.